ANALISIS KERAGAAN SISTEM USAHATANI BERBASIS LAHAN - R Sunsun Saefulhakim; Dyah Retno Panuju; Lutfi I Nasoetion (Jurnal Ilmu Tanah dan Lingkungan, 1999)
Efficiency and productivity are important terms in understanding the performance of the farming system. The landbased farming system is generally efficient and productive if it operates in a certain range of landholding scale. This study assumed that efficiency and productivity are related to farmland holding scale, land fragmentation, and cropping diversification. In a land-based farming system, land ownership holding scale and fragmentation and cropping diversification are assumed to have specific correlation. This study was conducted under a cooperation work between Research Institute of Bogor Agricultural University and Agency for Research and Development of Department of Agriculture, in research titled "Cropping Diversification and Employment Development, Stage 11". The study area comprised 6 (six) provinces, i.e.: North Sumatera, South Sumatera, Lampung, West Java, East Java, and South Sulawesi. From these provinces, it was sampled 12 districts. This study concludes that a lower level of efficiency, productivity, and farmer income is significantly related to a smaller scale of farmland ownership holding, highly fragmented land ownership holding, and miscoordinated (sprawl) land utilization pattern. Farmland tends to decrease every year, but the fragmentation of land ownership/holding tends to increase every year. In another way, miscoordinated land utilization pattern tends to expand. Therefore, the arrangement of land ownership/holding, consolidation of land, and coordination of land utilization are expected to be one of the effective policy instruments in solving current problems of land-based farming system's efficiency and productivity.